(3GdeONd GdJWHjbj ddbjGS aj GddjGbI GdHOfjIs - (3SdGeI EHQGgje CMeOs ((3GdGScfOQjIs (3efTCI GdeYGQas, 2000)
(3eLGdGJ GdbjGSaj GdJQHjI YGeI h GddjGbI GdHOfjI PGJ GdGQJHGW HGdUMI HTcd NGU,eHjfG CgejI GdJQHjI GdHOfjI dJaGOj CeQGV GdYUQ GdfGLeI Yf bdI GdMQcI, h eaghe GdJQcjH GdLSej ,h GdWQb GdejOGfjI dJMOjO fSHI GdOgf(B.s
Keywords: (3GddjGbI GdHOfjIs